High-Performance Birefringence of Periodic Nanostructures in FTO Thin Film Fabricated by IR-UV Femtosecond Laser - Zhang, Fengzhuo; Chen, Long; Zhang, Yuchan; Jiang, Qilin; Feng, Donghai; Zhang, Shian; Jia, Tianqing; Sun, Zhenrong; Xu, Hongxing (Frontiers in Physics, 2022)
By using infrared to ultraviolet (IR-UV) femtosecond laser directing, periodic nanostructures were efficiently fabricated on an F-doped tin oxide (FTO) film with a thickness of 650 nm. The morphology of the nanostructures and duty cycle were studied in detail by changing the laser fluence and scanning speed, where three lasers with central wavelengths of 343, 515, and 1,030 nm were used in the experiments. Under the 515 nm laser irradiation with scanning speed of 0.01 mm/s and laser fluence of 23 mJ/cm2, the periods Λ is 172 nm, the ablated nanogroove with width w2 is 52 nm, the birefringence Δn reached a maximum of 0.21, and the phase retardance was up to 135 nm. The morphology of the nanostructures and the birefringence effects of the FTO film prepared by a femtosecond laser at wavelengths of 1,030 and 343 nm were also studied, where the phase retardance of the nanostructured FTO film was much lesser than for the 515 nm laser because the thickness of the nanoripples layer, and, thus, the duty cycle of periodic nanoripples was smaller. Finally, a large-area FTO film with periodic nanostructures was fabricated efficiently by direct laser writing using a 515 nm fs laser beam focused via a cylindrical lens, and demonstrated the characteristics of a quarter-wave plate for 532 nm light.